Neuroinflammation in Alzheimer’s Disease: Current Progress in Molecular Signaling and Therapeutics - Thakur, Sujata; Dhapola, Rishika; Sarma, Phulen; Medhi, Bikash; Reddy, Dibbanti HariKrishna (Inflammation, 2023)
Alzheimer’s disease, a neurodegenerative disease with amyloid beta accumulation as a major hallmark, has become a dire global health concern as there is a lack of clear understanding of the causative agent. It is a major cause of dementia which is increasing exponentially with age. Alzheimer’s disease is marked by tau hyperphosphorylation and amyloid beta accumulation that robs people of their memories. Amyloid beta deposition initiated a spectrum of microglia-activated neuroinflammation, and microglia and astrocyte activation elicited expressions of various inflammatory and anti-inflammatory cytokines. Neuroinflammation is one of the cardinal features of Alzheimer’s disease. Pro-inflammatory cytokine signaling plays multifarious roles in neurodegeneration and neuroprotection. Induction of proinflammatory signaling leads to discharge of immune mediators which affect functions of neurons and cause cell death. Sluggish anti-inflammatory system also contributes to neuroinflammation. Numerous pathways like NFκB, p38 MAPK, Akt/mTOR, caspase, nitric oxide, and COX are involved in triggering brain immune cells like astrocytes and microglia to secrete inflammatory cytokines such as tumor necrosis factor, interleukins, and chemokines and participate in Alzheimer’s disease pathology. PPAR-γ agonists tend to boost the phagocytosis of amyloid beta and decrease the inflammatory cytokine IL-1β. Recent findings suggest the cross-link between gut microbiota and neuroinflammation contributing in AD which has been explained in this study. The role of cellular, molecular pathways and involvement of inflammatory mediators in neuroinflammation has also been described; targeting them could be a potential therapeutic strategy for treatment of AD.